2016
DOI: 10.2147/ndt.s97796
|View full text |Cite|
|
Sign up to set email alerts
|

Confirmation of the factorial structure of the Japanese short version of the TEMPS-A in psychiatric patients and general adults

Abstract: BackgroundThe Temperament Evaluation of the Memphis, Pisa, Paris, and San Diego Auto-questionnaire (TEMPS-A) is a 110-item questionnaire that assesses five affective temperaments. However, a valid shortened version is desired for large-scale investigations to enhance the compliance of respondents.MethodsA confirmatory factor analysis was conducted among 320 psychiatric patients and 61 general adults. The participants completed the Japanese 39-item short version of the TEMPS-A, and a portion of the participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…A possible interpretation of this discrepancy is that, in the study by Di Florio et al, the MDD group included only the subjects diagnosed with recurrent MDD with hypomanic features, because recurrent major depressive episodes is a predictor of bipolarity [18]. The utilization of the short version of the TEMPS-A may also explain the difference between the results of their studies and ours, as the short version of the TEMPS-A (39 items) shows only weak or moderate correlation with the full version of the TEMPS-A (109/110 items) [28].…”
Section: Plos Onementioning
confidence: 82%
“…A possible interpretation of this discrepancy is that, in the study by Di Florio et al, the MDD group included only the subjects diagnosed with recurrent MDD with hypomanic features, because recurrent major depressive episodes is a predictor of bipolarity [18]. The utilization of the short version of the TEMPS-A may also explain the difference between the results of their studies and ours, as the short version of the TEMPS-A (39 items) shows only weak or moderate correlation with the full version of the TEMPS-A (109/110 items) [28].…”
Section: Plos Onementioning
confidence: 82%
“…To assess cyclothymic and other temperaments, TEMPS-A short-version [ 41 ], which comprises 39 items instead of the 110 items in the full version), may have better usability. Moreover, further development of more straightforward and usable questionnaires that could distinguish cyclothymic temperament in patients with T2DM is required.…”
Section: Discussionmentioning
confidence: 99%
“…26 The Japanese short version of TEMPS-A was used in the present study. 15,27,28 The patients filled out the short version of TEMPS-A on their admission to hospital. To evaluate the severity of their depression at the time of answering the questionnaire, they also filled out the Japanese version of Patient Health Questionnaire-9 (PHQ-9).…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…26 On the other hand, a recent study on a group composed mostly of patients with psychiatric disorders reported that a firm factor structure was not identified in the shortened version of TEMPS-A, and that an alternative 18-item shorter version showed a firm factor structure. 27 The difference between the results of these two studies may be explained by the different characteristics of the included subjects.…”
mentioning
confidence: 96%